RISE: ReNeU's 1st anniversary - galvanising research excellence / Prof. Dr Nooritawati Md Tahir - Md Tahir, Nooritawati (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
It's ReNeU's 1st birthday! 16th June 2021 marked the one-year establishment of Research Nexus UiTM (ReNeU).